2008
DOI: 10.1007/s11270-008-9721-0
|View full text |Cite
|
Sign up to set email alerts
|

Tidal Hydrodynamics and their Implications for the Dispersion of Effluents in Mazatlán Harbor: An Urbanized Shallow Coastal Lagoon

Abstract: In order to investigate the Urias Coastal Lagoon (UCL) hydrodynamics, a vertically integrated semi-implicit, non-linear, finite difference model, has been applied. The flow dynamics in this model has been described by the depth integrated shallow water equations and has been forced by prescribed free surface elevations at the open boundary in the inlet of the lagoon. The predicted instantaneous tidal elevation and the vector field of tidal velocities, reflect reasonably well the flood and ebb conditions in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
26
0
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 13 publications
6
26
0
7
Order By: Relevance
“…1) and covers an area of 1800 ha (Montaño-Ley et al 2008). The region has a tropicalsubtropical climate and three seasons: rainy from July to October, dry-cold from November to April, and dry-warm from May to June.…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…1) and covers an area of 1800 ha (Montaño-Ley et al 2008). The region has a tropicalsubtropical climate and three seasons: rainy from July to October, dry-cold from November to April, and dry-warm from May to June.…”
Section: Study Areamentioning
confidence: 99%
“…1) y cubre una superficie de 1800 ha (Montaño-Ley et al 2008). El clima de la región es tropicalsubtropical y presenta un patrón que define tres épocas: lluviosa de julio a octubre, seca-fría de noviembre a abril y seca-cálida de mayo a junio.…”
Section: áRea De Estudiounclassified
See 1 more Smart Citation
“…The earlier studies of Montaño-Ley and Peraza-Vizcarra (1986) observed the net movement of sediment of 214,609 m 3 yr −1 south-eastward occasioned by changes in wave regimes, while Montaño-Ley and Gutiérrez-Estrada (1987) found erosional volumes of sediment with the maximum erosion at 15.7 m 3 per metre of length of the beach and Montaño-law et al (1988) observed an 8.5 m 3 of eroded sediments along the beach. Mazatlán coastline is characterized by mixed tide with an average range of about 1.0 m, a prevailing NW wind and occasional tropical storms migrating along the Pacific Coast of Mexico from SW striking the Mazatlán city (Montaño-Ley et al, 2008).…”
Section: Mazatlán Coastlinementioning
confidence: 99%
“…Numerical modeling has been extensively applied to simulate water circulation and contaminant transport in harbors and semi-enclosed coastal areas. For example, efforts were made to better understand the hydrodynamic regimes (Estacio et al, 1997;Vethamnoy et al, 2005;Azam et al, 2006a;Dias and Lopes, 2006a,b;Maraqa et al, 2008;Montano-Ley et al, 2008), to investigate pollutant dispersion (Gesteira-Gomez et al, 1999;Das et al 2000), and to assess water quality (Tao et al, 2001;Copeland et al, 2003;Fiandrino et al, 2003;Lopes et al, 2005;Cerejo and Dias, 2007). Other efforts were made to establish surveillance procedures (Lopes et al, 2005) and to quantify the impact of effluent discharge (Ganoulis, 1991;Kashefipour et al, 2002;Gupta et al, 2004, Kashefipour et al, 2006Rucinski et al, 2007;Brewer et al, 2008 …”
Section: Governing Equationsmentioning
confidence: 99%